Considerations for the Formulation of Fiqh Munakahat Reason and Criminal Law on Polygamy Sirri Practices in Indonesia - Moh. Mujibur Rohman; Aziz Basuki (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
Polygamy in Islam is legal with the condition that it must be fair. In practice, justice is rarely realised. This is what makes the state take a preventive stance by obtaining permission from the first wife. The difficulty of obtaining permission makes sirri polygamy a practice under the pretext of religious syi'ar, even though the danger is the neglect of women and their offspring. This research is a normative research with a statutory approach, analytical approach and conceptual approach which is then reduced, displayed and drawn conclusions on the data obtained. The results of the study state that administratively the perpetrators of nikah sirri are criticised by religion, because in the Islamic concept marriage must be carried out openly (i'lan al-nikah) and administratively the state of marriage must be carried out at the marriage registrar, both at the Dukcapil and at the KUA. Meanwhile, the sanction for those who commit polygamy sirri or underhand is imprisonment for a maximum of six years or punishment in the form of compensation or a fine of Rp. 200,000,000 (two hundred million rupiah), this refers to article 126 of Law No. 1 of 2023 concerning the Criminal Code (KUHP). This research is expected to be a reference for policy makers in formulating regulations that are more comprehensive and effective in overcoming the problem of sirri polygamy, as well as for legal practitioners in providing legal assistance for victims.